2014
DOI: 10.18488/journal.61/2014.2.7/61.7.147.158
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Preparation Programs and Technology Integration: Best Practices for Curriculum Design

Abstract: Differences in teacher preparation program design were investigated by researching conceptions of technology integration for pre-service teachers in both undergraduate and graduate programs. Participants responded to surveys regarding their technology skills and ideas about technology integration both at the beginning of their program coursework and after completing the technology requirement of their degree program. Responses were analyzed by program and graduate/undergraduate status in order to assess the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…She noted that high selfefficacy is essential to successful technology integration. This is also supported by Schnackenberg and Still's (2014) study of teacher preparation programs and technology integration which found a significant, positive correlation between positive perceptions of ability to integrate technology and technology skills that encourage more meaningful interactions.…”
Section: Self-efficacy Theorymentioning
confidence: 70%
See 4 more Smart Citations
“…She noted that high selfefficacy is essential to successful technology integration. This is also supported by Schnackenberg and Still's (2014) study of teacher preparation programs and technology integration which found a significant, positive correlation between positive perceptions of ability to integrate technology and technology skills that encourage more meaningful interactions.…”
Section: Self-efficacy Theorymentioning
confidence: 70%
“…The effects of professional learning experiences on teacher's self-efficacy is a key component of technology integration Schnackenberg & Still, 2014;). extensive research into self-efficacy draws connections to the importance of strong academic, instructional, and technological efficacy in order for teachers to successfully engage in the educational shift described in the following quote.…”
Section: Self-efficacy Theorymentioning
confidence: 99%
See 3 more Smart Citations